Antipyretic and Antianemic Activities of Three Anti-malaria Recipes from South Benin on Wistar Rats - Medoatinsa, Seindé E.; AGBANGNAN, DOSSA COKOU PASCAL; ATCHADE, SOSSA PASCAL; BOGNINOU AGBIDINOUKOUN, G. SOPHIE REINE; DOSSEH, KOSSIVI; KPATCHA, Tchazou; AGBONON, Amegnona; AHISSOU, HYACINTHE; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2017)
The present study aims to evaluate "in vivo" the acute toxicity, antipyretic and antianemic activities of three plant recipes used in the treatment of malaria in southern Benin lake cities on Wistar rats. We note the presence of saponosides, phenolic compounds, sterols and terpenes in the recipes studied. The toxicity evaluation of the extracts revealed that they are practically non-toxic (LD50> 5g/kg body weight) according to the Hodge and Sterner classification. All the extracts investigated contain antipyretic molecules but only two extracts (aqueous extract obtain by decoction of the child's recipe: 36.07 ± 0.48°C, hydroethanolic macerated of the adult’s recipe: 36.07 ± 0.33°C) showed significant antipyretic activity, similar to that of aspirin (36.03 ± 0.25°C) used as reference molecule in the present study. After evaluating the antianemic activity, we note that the extracts are not hemolytic.
Keywords: Toxicity; antipyretic; antianemic; metabolites; plants; malaria